Passivation contact composite layer and perovskite-crystalline silicon laminated solar cell

By using the stacked structure of SiO2 tunneling layer, ZnO-based electron selective transport layer and hydrogen passivation cap layer in perovskite-crystalline silicon stacked solar cells, the problems of silicon thin film passivation contact and traditional intermediate composite layer materials are solved, and a low-cost, simple process and high-performance passivation contact composite layer is realized.

CN119653924APending Publication Date: 2025-03-18SUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411756088.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In existing perovskite-crystalline silicon stacked solar cells, the passivation contact of silicon thin films leads to large parasitic absorption losses, complex processes and high costs, and traditional intermediate composite layer materials such as ITO and IZO have high cost and high lateral conductivity problems, which limits battery performance and application.

Method used

The stacked structure of SiO2 tunneling layer, ZnO-based electron-selective transport layer and hydrogen passivation cap layer is used as the passivation contact composite layer, and is prepared by the atomic layer deposition method to achieve appropriate energy level matching and good light transmission, reduce parasitic absorption, and improve carrier recombination performance through doping regulation.

Benefits of technology

It realizes a passivation contact composite layer with a low-cost and simple process, reduces parasitic absorption, improves carrier recombination performance, and is suitable for the preparation of large-area perovskite-crystalline silicon stacked solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653924A_ABST
    Figure CN119653924A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solar cells, and particularly relates to a passivation contact composite layer and a perovskite-crystalline silicon laminated solar cell. According to the passivation contact composite layer structure, surface passivation, electron selective transmission and carrier recombination of the silicon-bottom battery can be realized at the same time. The passivation contact composite layer comprises a SiO2 tunneling layer, a ZnO-based electron selective transmission layer and a hydrogen passivation cover layer. The wide-band-gap ZnO-based electron selective transmission layer can avoid the problem of optical parasitic absorption caused by passivation contact of the silicon thin film and has high electron concentration and bulk conductivity, and the ZnO-based electron selective transmission layer can further optimize the optical and electrical properties of the ZnO-based electron selective transmission layer by doping one or more of B, Al, Ga and H elements. In addition, in order to form good contact, the hydrogen passivation cap layer can be reserved or removed according to the conductivity type and the device structure. The ZnO-based electron selective transmission layer can be covered with interface layers such as MgOx, Mg, Al or Ti, so that the carrier recombination effect is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cells, and in particular relates to a passivation contact composite layer and a perovskite-crystalline silicon stacked solar cell. Background Art

[0002] Develop clean and low-cost photovoltaic power generation. The photoelectric conversion efficiency of mainstream crystalline silicon solar cells has approached its limit. Perovskite-crystalline silicon tandem solar cells combine the advantages of perovskite cells with adjustable band gaps with mature crystalline silicon cells, improve the utilization of the solar spectrum, break through the theoretical limit efficiency of silicon cells, and reduce the preparation cost of solar cells. They have broad application prospects.

[0003] On the one hand, the crystalline silicon bottom cells commonly used in perovskite-crystalline silicon tandem solar cells include silicon heterojunction cells (SHJ) and tunneling silicon oxide (SiO2) passivation contact (TOPCon) cells. Both use doped silicon film to construct passivation contact, where SHJ is composed of intrinsic hydrogenated amorphous silicon (a-Si:H) superimposed with doped a-Si:H, and TOPCon is composed of tunneling SiO2 superimposed with doped microcrystalline (poly) silicon. The parasitic absorption of silicon film in SHJ and TOPCon technology is large, resulting in a short circuit current (J sc ) is low. At the same time, the deposition equipment of thin-film silicon, including plasma enhanced chemical vapor deposition (PECVD) or low-pressure chemical vapor deposition (LPCVD), is expensive and involves toxic and flammable gases (such as silane, phosphine and borane). In addition, the SHJ technology has a narrow process window and poor thermal stability (250°C). The low-temperature silver paste used is expensive and has poor tensile strength. The TOPCon structure has a high annealing temperature (800°C-1000°C) and many process steps, resulting in a high fragmentation rate during the production process, which in turn limits the use of thin silicon wafers. Therefore, the development of a new passivation contact structure based on metal compounds is crucial to further improve the performance of silicon-bottom cells and thus improve the performance of perovskite-crystalline silicon stacked cells (TG Allen, J. Bullock, X. Yang, et al., Nat. Energy 2019, 4, 914; K. Gao, Q. Bi, X. Wang, et al., Adv. Mater. 2022, 34, 2200344.).

[0004] On the other hand, the intermediate composite layer material of perovskite-crystalline silicon tandem solar cells usually uses transparent conductive metal oxide films (such as indium tin oxide ITO, indium zinc oxide IZO, etc.) as the intermediate composite layer. ITO and IZO are widely used because of their excellent optoelectronic properties, but their optical parasitic absorption is large, and they contain rare metal indium, which is expensive; and ITO and IZO have good lateral conductivity, which is easy to cause leakage when preparing large-area tandem cells, limiting their application. Therefore, doped polycrystalline silicon or amorphous silicon thin film tunneling junctions are introduced into perovskite-crystalline silicon tandem cells to replace the traditional ITO / IZO intermediate layer, and perovskite-TOPCon tandem cells and perovskite-heterojunction tandem cells with efficiencies of up to 29.22% and 31.25% are prepared, respectively (J. Zheng, et al. Nature Energy. 2023, 8, 1250; X. Yin, et al. Science 2023, 381, 59). This new tunneling composite layer has excellent passivation and contact properties, and has the advantage of low lateral conductivity, which is suitable for the preparation of large-area tandem cells. However, it also has problems such as high preparation cost and large parasitic absorption. In the research of perovskite-crystalline silicon tandem solar cells, developing a new intermediate composite layer material that has both high transmittance and good carrier recombination performance is crucial to improving the performance of tandem cells and reducing costs.

[0005] In summary, the development of metal compound-based transparent passivation contacts with composite layer functions is crucial to simplifying the preparation process of crystalline silicon-perovskite tandem cells, reducing costs, and further improving their photoelectric conversion efficiency.

[0006] Passivation contact of silicon bottom cell: (1) TOPCon cell realizes passivation and selective transport of carriers simultaneously through SiO2 / doped Poly silicon; (2) SHJ cell uses intrinsic a-Si:H / doped a-Si:H to realize passivation contact function; (2) Metal oxide-based passivation contact based on TiO2, MgO, etc. uses the low work function of metal compounds to realize selective transport of electrons;

[0007] Intermediate composite layer of stacked cells: (1) At present, there are two main types of intermediate composite layer materials for perovskite-crystalline silicon stacked cells. The first is an intermediate composite layer based on doped indium oxide (ITO or IZO). ITO is widely used due to its excellent optoelectronic properties and mature preparation process, but it contains rare metal indium and has a high cost. (2) The second is a tunnel junction based on doped silicon film: the band bending of doped p-type and n-type microcrystalline silicon or polycrystalline silicon film is used to form a tunnel junction to achieve efficient carrier recombination. The doped silicon film tunnel junction has good longitudinal carrier transport performance and low lateral conductivity, which is suitable for the preparation of large-area stacked cells.

[0008] The current technology has the following problems:

[0009] 1. Passivation contacts based on silicon films, including SiO2 / doped Poly silicon or a-Si:H(i) / doped a-Si:H, will lead to parasitic light absorption losses; the process is more complicated and the cost is higher.

[0010] 2. The passivation performance of the metal compound-based passivation contacts currently developed for crystalline silicon cells is poor;

[0011] 3. The high cost of indium oxide-doped intermediate composite layers (ITO and IZO) limits their widespread use.

[0012] 4. The indium oxide-doped intermediate composite layer (ITO and IZO) has high lateral conductivity, which is easy to cause leakage in large-area stacked batteries, limiting its application;

[0013] 5. The parasitic absorption of the indium oxide-doped intermediate composite layer (ITO and IZO) in the near-infrared band is large, which limits the current density of the crystalline silicon bottom battery. It is usually prepared by magnetron sputtering, which causes certain sputtering damage to the crystalline silicon bottom battery, limiting its performance.

[0014] 6. The tunnel junction of doped silicon thin film needs to have a higher doping concentration to form a strong band bending. Therefore, the carrier concentration of the film is higher and the optical parasitic absorption is larger, which limits the current density of the crystalline silicon bottom battery and its preparation cost is higher. Summary of the invention

[0015] The present invention aims to provide a laminated structure having both the electronic passivation contact function of a crystalline silicon bottom cell and the function of an upper and lower sub-cell composite layer, and a preparation method thereof, and a perovskite-crystalline silicon laminated cell having the structure. The laminated structure specifically includes a SiO2 tunneling layer, a ZnO base layer and a hydrogen passivation cap layer. The laminated structure has suitable energy level matching, good light transmittance, small parasitic absorption, excellent carrier recombination performance, and has the advantages of low preparation cost and simple process. The ZnO base layer can be prepared by an atomic layer deposition method, which has a simple preparation process and less deposition damage. Its photoelectric performance can be controlled by adjusting the doping elements and proportions as well as deposition parameters (gas pressure, doping ratio, deposition temperature, etc.), thereby achieving excellent carrier recombination performance. Compared with the commonly used passivation contact based on doped silicon film and TiO x ,MgO x Compared with other metal compound passivation contacts, ZnO-based passivation contacts have the advantages of small parasitic light absorption and excellent passivation performance; compared with the commonly used doped indium oxide composite layer and doped silicon thin film tunnel junction, the ZnO-based intermediate composite layer has the advantages of simple preparation process, low cost, and small optical parasitic absorption; and its lateral conductivity is adjustable, which is suitable for the preparation of large-area perovskite-crystalline silicon stacked cells.

[0016] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0017] The present invention provides a passivation contact composite layer, wherein the passivation contact composite layer structure is arranged on the surface of a silicon substrate, and comprises a SiO2 tunneling layer, a ZnO-based electron selective transport layer and a hydrogen passivation cap layer which are deposited in sequence; the hydrogen passivation cap layer comprises Al2O3, TiO2 and SiN x One or more of the above, the hydrogen passivation cap layer is removed by wet removal or dry etching or not; the wet removal method is a sodium carbonate solution heating immersion treatment.

[0018] Preferably, the ZnO-based electron selective transport layer is selected from an intrinsic ZnO layer or a doped ZnO layer.

[0019] Furthermore, in the doped ZnO layer, the doping element is selected from one or more of Al, B, Ga and H, and the doping atomic concentration is 1-20%.

[0020] Furthermore, the ZnO-based electron selective transport layer is deposited by atomic layer deposition, and the thickness and doping concentration of the doped ZnO layer are controlled by the number of super cycles in the atomic layer deposition super cycle mode and the cycle ratio in the doping sub-cycle.

[0021] Furthermore, the doping element is Al, the doping cycle ratio of ZnO to Al2O3 in the atomic layer deposition super cycle mode is 5-100:1; the number of super cycles in the atomic layer deposition super cycle mode is 2-50 times; and the doping atomic concentration of the boron element is 1-20%.

[0022] Preferably, the silicon substrate is selected from a planar silicon substrate or a textured silicon substrate.

[0023] Preferably, the thickness of the ZnO-based electron selective transport layer is 1-200 nm, the thickness of the SiO2 tunneling layer is 0.5-2 nm, and the thickness of the hydrogen passivation cap layer is 5-200 nm.

[0024] Preferably, in the hydrogen passivation cap layer, Al2O3 and TiO2 are obtained by atomic layer deposition, and SiN x Obtained by plasma chemical vapor deposition.

[0025] Preferably, the preparation method of the SiO2 tunneling layer is a dry method or a wet method; the dry method is selected from thermal oxidation, ozone oxidation or chemical vapor deposition, and the wet method is selected from nitric acid oxidation.

[0026] Preferably, a high electron concentration interface layer may be superimposed on the hydrogen passivation cap layer, and the high electron concentration interface layer is MgO x, metal Mg, metal Al or metal Ti. After removing the hydrogen passivation cap layer, a high electron concentration metal layer or a metal compound layer is further introduced to promote carrier recombination between the upper and lower sub-batteries.

[0027] The present invention also provides a perovskite-crystalline silicon tandem solar cell, wherein the light-receiving surface of the silicon bottom cell of the perovskite-crystalline silicon tandem solar cell has the above-mentioned passivation contact composite layer.

[0028] Specifically, the above-mentioned perovskite-crystalline silicon tandem solar cell adopts the passivation contact composite layer as the electron passivation contact of the silicon bottom cell and the intermediate composite layer of the tandem cell, and the hole passivation contact of the silicon bottom cell adopts one of a-Si:H(i) / a-Si:H(p), SiO2 / Poly(p), and p-type doped homojunction.

[0029] The technical solution of the present invention has the following advantages over the prior art:

[0030] Low preparation cost: Composite layers such as ITO and IZO are expensive, while the ZnO-based layer provided in the present invention has low preparation cost.

[0031] Small parasitic absorption and no sputtering damage: SiO2 / ZnO-based passivation contact is a wide bandgap (>3.0eV) material with high transparency. It can significantly reduce parasitic light absorption loss; at the same time, both the ZnO base layer and the hydrogen passivation cap layer can be prepared by atomic layer deposition without sputtering damage.

[0032] Simple process: The SiO2 / ZnO-based passivation contact composite layer combines the electronic passivation contact structure of the silicon bottom battery and the middle composite layer of the stacked battery into one, which simplifies the preparation process.

[0033] The passivation contact composite layer structure of the present invention has excellent surface passivation performance, and realizes surface passivation, electron selective transmission and intermediate composite layer of silicon bottom battery at the same time. The wide bandgap ZnO-based electron selective transmission layer can avoid the optical parasitic absorption problem caused by silicon thin film, and has high electron concentration and bulk conductivity. The ZnO-based electron selective transmission layer can further optimize its optical and electrical properties by doping. By doping elements such as B, Al, Ga and H, the electron concentration and bulk conductivity of the ZnO-based electron selective transmission layer are improved, and its work function is reduced to further induce the silicon conduction band to bend downward, thereby reducing the electron transmission barrier. Reasonable regulation of the doping cycle ratio and thickness of the ZnO base layer can obtain low contact resistance. In addition, the hydrogen passivation cap layer can be selectively retained or removed according to the conductivity type and device structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a structural diagram of a passivation contact composite layer on a planar silicon substrate of Example 1.

[0035] Figure 2 This is a diagram of a method for preparing a passivation contact composite layer on a planar silicon substrate of Example 1.

[0036] Figure 3 This is a structural diagram of the passivation contact composite layer on the textured silicon substrate of Example 2.

[0037] Figure 4 This is a diagram of the preparation method of the passivation contact composite layer on the textured silicon substrate of Example 2.

[0038] Figure 5 This is a diagram of a perovskite-crystalline silicon stacked solar cell with a passivated contact composite layer structure on a planar silicon substrate of Example 3.

[0039] Figure 6 This is a diagram of the preparation method of a perovskite-crystalline silicon tandem solar cell having a passivated contact composite layer structure on a planar silicon substrate of Example 3.

[0040] Figure 7 This is the JV curve diagram of Example 3.

[0041] Figure 8 This is a diagram of a perovskite-crystalline silicon stacked solar cell with a passivated contact composite layer structure on a textured silicon substrate of Example 4.

[0042] Fig. 9 This is a diagram of the preparation method of the perovskite-crystalline silicon tandem solar cell with a passivation contact composite layer structure on a textured silicon substrate of Example 4.

[0043] Fig.10 This is a diagram of a perovskite-crystalline silicon tandem solar cell with a passivated contact composite layer structure according to Example 5.

[0044] Fig.11 This is a diagram of the preparation method of the perovskite-crystalline silicon tandem solar cell with a passivated contact composite layer structure of Example 5.

[0045] Fig.12 This is a diagram of a perovskite-crystalline silicon tandem solar cell with a passivated contact composite layer structure according to Example 6.

[0046] Fig.13 This is a diagram of the preparation method of the perovskite-crystalline silicon tandem solar cell with a passivated contact composite layer structure of Example 6.

[0047] Description of reference numerals: 101-n-type silicon substrate, 102-SiO2 tunneling layer, 103-AZO layer, 201-n-type silicon substrate, 202-SiO2 tunneling layer, 203-gallium-doped zinc oxide (GZO) layer, 301-silicon substrate, 302-p +Emitter, 303-Al2O3 passivation layer, 304-SiNx anti-reflection film, 305-SiO2 tunnel passivation layer, 306-AZO layer, 307-self-assembled small molecule layer, 308-perovskite light absorption layer, 309-C 60 Electron transport layer, 310-SnO2 electron transport layer, 311-Zn-doped indium oxide transparent electrode, 312-metal silver electrode, 313-silver electrode, 314-magnesium fluoride anti-reflection layer, 401-silicon substrate, 402-p + Emitter, 403-Al2O3 passivation layer, 404-SiNx anti-reflection film, 405-SiO2 tunnel passivation layer, 406-GZO layer, 407-self-assembled small molecule layer, 408-perovskite light absorption layer, 409-C 60 Electron transport layer, 410-SnO2 electron transport layer, 411-Zn-doped indium oxide transparent electrode, 412-Metallic silver electrode, 413-Silver electrode, 414-Magnesium fluoride anti-reflection layer, 501-Silicon substrate, 502-p-type emitter, 503-Al2O3 passivation layer, 504-SiNx anti-reflection film, 505-SiO2 tunneling passivation layer, 506-Boron-doped zinc oxide layer, 507-Metallic Mg layer, 508-Self-assembled small molecule layer, 509-Perovskite light absorption layer, 510-C 60 Electron transport layer, 511-SnO2 electron transport layer, 512-Zn-doped indium oxide transparent electrode, 513-Metallic silver electrode, 514-Silver electrode, 515-Magnesium fluoride anti-reflection layer, 601-n-type silicon substrate, 602-SiO2 tunneling layer, 603-AZO layer, 604-a-Si:H(i) passivation layer, 605-Boron-doped nc-Si:H(P) layer, 606-ITO transparent electrode, 607-Silver electrode, 608-Self-assembled small molecule layer, 609-Perovskite light absorption layer, 610-C 60 Electron transport layer, 611-SnO2 electron transport layer, 612-zinc-doped indium oxide transparent electrode, 613-silver electrode, 614-magnesium fluoride anti-reflection layer. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0049] Example 1

[0050] This embodiment provides a passivation contact composite layer structure on a planar silicon substrate and a preparation method thereof, such as Figure 1 and Figure 2 The specific preparation method is as follows:

[0051] (1) An n-type single crystal silicon wafer is selected, a 10 wt% NaOH aqueous solution is used to perform polishing and etching to remove a damaged layer of the silicon wafer, and then the silicon wafer is cleaned by an RCA method to obtain an n-type silicon substrate 101;

[0052] (2) A SiO2 tunneling layer 102 is oxidized on the surface of the silicon wafer by a thermal oxidation method, wherein the SiO2 thickness is 1.5 nm, the temperature is 500° C., and the time is 15 min;

[0053] (3) The processed n-type silicon substrate is placed in an ALD (atomic layer deposition system) chamber to prepare an AZO layer 103 (aluminum-doped zinc oxide) by a super cycle method. The deposition temperature is 200°C, the gas pressure is 50mToor, the deposition cycle ratio of Al2O3 and ZnO is 24:1, and the super cycle number is 1; the Al2O3 cap layer (which will be removed later) is deposited by ALD. Figure 1 Not shown), the deposition temperature is 200°C, the gas pressure is 50 mToor, and the deposition cycle number is 300;

[0054] (4) The sample was placed in an atmosphere annealing furnace and annealed for 30 min at 500 °C in a N2 / H2 (95% / 5%) atmosphere;

[0055] (5) Prepare 0.1 M Na2CO3 solution, heat it to 60 °C, and immerse the sample in the solution for 8 min to remove the Al2O3 capping layer so as to form good contact later;

[0056] Thus, the SiO2 / AZO passivation contact composite layer provided by the present invention is formed. The passivation contact composite layer structure has ultra-high transparency and excellent passivation effect, and can achieve a composite current density of J02fA / cm 2 , implicit open circuit voltage iV oc 742 mV.

[0057] Example 2

[0058] This embodiment provides a passivation contact composite layer structure on a textured silicon substrate and a preparation method thereof, such as Figure 3 and Figure 4 The specific preparation method is as follows:

[0059] (1) An n-type single crystal silicon wafer is selected, a 10% (wt)-NaOH aqueous solution is used for polishing and etching to remove the damaged layer of the silicon wafer, and then a 2% (wt)-NaOH solution is used to prepare a pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method (wet chemical cleaning method) to obtain an n-type silicon substrate 201;

[0060] (2) A SiO2 tunneling layer 202 is oxidized on the surface of the silicon wafer by a thermal oxidation method, wherein the SiO2 thickness is 1.5 nm, the temperature is 500° C., and the time is 15 min;

[0061] (3) The treated n-type silicon substrate is placed in an ALD chamber to prepare a gallium-doped zinc oxide layer 203 (GZO) by a super-cycle method, with a deposition temperature of 200°C, a gas pressure of 50 mToor, a deposition cycle ratio of Ga2O3 and ZnO of 24:1, and a super-cycle number of 1; an Al2O3 cap layer (which will be removed later) is continuously deposited by ALD. Figure 3 Not shown), the deposition temperature is 200°C, the gas pressure is 50 mToor, and the deposition cycle number is 300;

[0062] (4) The sample was placed in an atmosphere annealing furnace and annealed for 30 min at 500 °C in a N2 / H2 (95% / 5%) atmosphere;

[0063] (5) Prepare 0.1 M Na2CO3 solution, heat it to 60 °C, and immerse the sample in the solution for 8 min to remove the Al2O3 capping layer so as to form good contact later;

[0064] Thus, the SiO2 / GZO passivation contact composite layer provided by the present invention is formed. The passivation contact composite layer structure has ultra-high transparency; excellent passivation effect, implicit open circuit voltage iV oc 730 mV.

[0065] Example 3

[0066] This embodiment provides a perovskite-crystalline silicon tandem solar cell having the passivation contact composite layer structure on a planar silicon substrate and a method for preparing the same. The tandem cell structure and the method for preparing the same given in this embodiment are as follows: Figure 5 and Figure 6 As shown. The stacked cell uses a p-type doped homojunction prepared on an n-type silicon substrate as a silicon bottom cell hole passivation contact. The structure acts as an electron passivation contact and also has a composite layer function. A wide bandgap perovskite top cell is superimposed, and grid-line silver electrodes are used on the front and back of the cell. The perovskite-crystalline silicon stacked cell preparation method is as follows:

[0067] (1) An n-type crystalline silicon substrate is selected, and a 10% (wt)-NaOH aqueous solution is used to etch and remove the surface damage layer, and then a 2% (wt)-NaOH solution is used to prepare a micron pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain a silicon substrate 301;

[0068] (2) Place the silicon substrate in a tube furnace and diffuse boron to prepare p + Emitter 302, diffusion temperature 900°C, square resistance about ~100Ω / sq;

[0069] (3) using a diluted hydrofluoric acid solution to remove the surface borosilicate glass and using single-sided alkaline polishing to remove the back p-type emitter and pyramid velvet;

[0070] (4) depositing an Al2O3 passivation layer 303 on the back side by ALD process, with a thickness of 10 nm and a deposition temperature of 200°C;

[0071] (5) using PECVD to deposit a SiNx anti-reflection film 304 on the back surface, with a thickness of 65 nm and a deposition temperature of 400°C;

[0072] (6) using ultraviolet ozone oxidation to oxidize a SiO2 tunnel passivation layer 305 on the front side of the silicon wafer, the SiO2 thickness is 1.5 nm, the temperature is room temperature, and the oxidation time is 15 min;

[0073] (7) The AZO layer 306 was prepared by ALD super-cycle method, with a deposition temperature of 200°C, a gas pressure of 50 mToor, a deposition cycle ratio of Al2O3 and ZnO of 24:1, a super-cycle number of 1, and an AZO thickness of 5 nm; an Al2O3 cap layer was deposited by ALD (which will be removed later). Figure 5 Not shown), the deposition temperature is 200°C, the gas pressure is 50 mToor, and the deposition cycle number is 300;

[0074] (8) Annealing in an atmosphere annealing furnace at 500°C in a N2 / H2 (95% / 5%) atmosphere for 30 min;

[0075] (9) Prepare 0.1 M Na2CO3 solution, heat it to 60 °C, and immerse the sample in the solution for 8 min to remove the Al2O3 capping layer so as to form good contact later;

[0076] (10) using a spin coating method to prepare a self-assembled small molecule layer 307 as a hole transport layer of the top battery;

[0077] (11) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 308 has a band gap of about 1.68 eV;

[0078] (12) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 309, thickness 20 nm;

[0079] (13) Atomic layer deposition was used to deposit C 60 A SnO2 electron transport layer 310 is deposited thereon at a deposition temperature of 100°C and a thickness of 20nm;

[0080] (14) depositing a zinc-doped indium oxide transparent electrode 311 (IZO) with a thickness of 100 nm on the SnO2 electron transport layer by magnetron sputtering;

[0081] (15) A metal silver electrode 312 is prepared on the back by screen printing; a silver electrode 313 is prepared on the front by high-temperature thermal evaporation on the zinc-doped indium oxide transparent electrode 311, and both adopt a grid-line distributed electrode pattern design;

[0082] (16) Finally, a magnesium fluoride anti-reflection layer 314 with a thickness of 20 nm is deposited on the silver electrode 313 by high temperature thermal evaporation.

[0083] Thus, a perovskite-crystalline silicon tandem solar cell with the passivation contact composite layer structure is formed. 2 The device can achieve a photoelectric conversion efficiency of 28.9%, which is 0.3% higher than the standard sample battery with TOPCon as the base cell and ITO as the composite junction. The open circuit voltage, short circuit current density and fill factor are 1.837V and 20.3mA / cm 2 , 77.54%, and its JV curve is as follows Figure 7 shown.

[0084] Example 4

[0085] This embodiment provides a perovskite-crystalline silicon tandem solar cell having the passivation contact composite layer structure on a textured silicon substrate and a method for preparing the same. The tandem cell structure and the method for preparing the same are shown in FIG. Figure 8 and Fig. 9 As shown. The stacked cell uses a p-type doped homojunction prepared on an n-type silicon substrate as a silicon bottom cell hole passivation contact. The structure acts as an electron passivation contact and also has a composite layer function. A wide bandgap perovskite top cell is superimposed, and grid-line silver electrodes are used on the front and back of the cell. The perovskite-crystalline silicon stacked cell preparation method is as follows:

[0086] (1) An n-type crystalline silicon substrate is selected, and a 10% (wt)-NaOH aqueous solution is used to etch and remove the surface damage layer, and then a 2% (wt)-NaOH solution combined with an additive is used to prepare a submicron pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain a silicon substrate 401;

[0087] (2) Place the silicon substrate in a tube furnace and diffuse boron to prepare p + Emitter 402, diffusion temperature 900°C, square resistance about ~100Ω / sq;

[0088] (3) using a diluted hydrofluoric acid solution to remove the surface borosilicate glass and using single-sided alkaline polishing to remove the back p-type emitter;

[0089] (4) depositing an Al2O3 passivation layer 403 on the back side by ALD process, with a thickness of 10 nm and a deposition temperature of 200°C;

[0090] (5) using PECVD to deposit a SiNx anti-reflection film 404 on the back side, with a thickness of 65 nm and a deposition temperature of 400°C;

[0091] (6) using ultraviolet ozone oxidation to oxidize a SiO2 tunnel passivation layer 405 on the front side of the silicon wafer, the SiO2 thickness is 1.5 nm, the temperature is room temperature, and the oxidation time is 15 min;

[0092] (7) The GZO layer 406 was prepared by ALD super-cycle method, with a deposition temperature of 200°C, a gas pressure of 50 mToor, a deposition cycle ratio of Ga2O3 and ZnO of 24:1, a super-cycle number of 1, and a GZO thickness of 5 nm; an Al2O3 cap layer was deposited by ALD (which will be removed later). Figure 8 Not shown), the deposition temperature is 200°C, the gas pressure is 50 mToor, and the deposition cycle number is 300;

[0093] (8) Annealing in an atmosphere annealing furnace at 500°C in a N2 / H2 (95% / 5%) atmosphere for 30 min;

[0094] (9) Prepare 0.1 M Na2CO3 solution, heat it to 60 °C, and immerse the sample in the solution for 8 min to remove the Al2O3 capping layer so as to form good contact later;

[0095] (10) using a spin coating method to prepare a self-assembled small molecule layer 407 as a hole transport layer of the top battery;

[0096] (11) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 408 has a band gap of about 1.68 eV;

[0097] (12) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 409, thickness 20 nm;

[0098] (13) Depositing a SnO2 electron transport layer 410 on C60 by atomic layer deposition at a deposition temperature of 100°C and a thickness of 20 nm;

[0099] (14) depositing a zinc-doped indium oxide transparent electrode 411 (IZO) with a thickness of 100 nm on the SnO2 electron transport layer by magnetron sputtering;

[0100] (15) A metal silver electrode 412 is prepared on the back by screen printing; a silver electrode 413 is prepared on the zinc-doped indium oxide transparent electrode 411 by high-temperature thermal evaporation on the front, and both adopt a grid-line distributed electrode pattern design;

[0101] (16) Finally, a magnesium fluoride anti-reflection layer 414 with a thickness of 20 nm is deposited on the silver electrode 413 by high temperature thermal evaporation.

[0102] At this point, the perovskite-crystalline silicon tandem solar cell with the passivation contact composite layer structure is formed.

[0103] Example 5

[0104] This embodiment provides a perovskite-crystalline silicon tandem solar cell having the passivation contact composite layer structure and a method for preparing the same. The tandem cell structure and the method for preparing the same given in this embodiment are as follows: Fig.10 and Fig.11 As shown. The stacked cell uses a p-type doped homojunction prepared on an n-type silicon substrate as a silicon bottom cell hole passivation contact, and the structure is used as an electron passivation contact. At the same time, an ultra-thin metal layer is introduced to enhance the carrier recombination effect, and a wide bandgap perovskite top cell is superimposed. The front and back of the cell use grid-line silver electrodes. The perovskite-crystalline silicon stacked cell preparation method is as follows:

[0105] (1) An n-type crystalline silicon substrate is selected, and a 10% (wt)-NaOH aqueous solution is used to etch and remove the surface damage layer, and then a 2% (wt)-NaOH solution is used to prepare a pyramid velvet surface, and then the silicon wafer is cleaned by an RCA method to obtain a silicon substrate 501;

[0106] (2) placing the silicon substrate in a tube furnace for boron diffusion to prepare a p-type emitter 502, the diffusion temperature is 900° C., and the square resistance is about 100 Ω / sq;

[0107] (3) using a diluted hydrofluoric acid solution to remove the surface borosilicate glass and using single-sided alkaline polishing to remove the back p-type emitter and pyramid velvet;

[0108] (4) depositing an Al2O3 passivation layer 503 on the front surface by ALD process, with a thickness of 10 nm and a deposition temperature of 200°C;

[0109] (5) using PECVD to deposit a SiNx anti-reflection film 504 on the front surface with a thickness of 65 nm and a deposition temperature of 400°C;

[0110] (6) using ultraviolet ozone oxidation to oxidize a SiO2 tunnel passivation layer 505 on the front side of the silicon wafer, the SiO2 thickness is 1.5 nm, the temperature is room temperature, and the oxidation time is 15 min;

[0111] (7) A boron-doped zinc oxide layer 506 (BZO) was prepared by ALD super-cycle method, with a deposition temperature of 200°C, a gas pressure of 50 mToor, a deposition cycle ratio of B2O3 and ZnO of 24:1, a super-cycle number of 1, and a BZO thickness of 5 nm; an Al2O3 cap layer (which will be removed later) was deposited by ALD. Fig.10 Not shown), the deposition temperature is 200°C, the gas pressure is 50 mToor, and the deposition cycle number is 300;

[0112] (8) Annealing in an atmosphere annealing furnace at 500°C in a N2 / H2 (95% / 5%) atmosphere for 30 min;

[0113] (9) Prepare 0.1 M Na2CO3 solution, heat it to 60 °C, and immerse the sample in the solution for 8 min to remove the Al2O3 capping layer so as to form good contact later;

[0114] (10) using thermal evaporation to evaporate a metal Mg layer 507 with a thickness of 2 nm;

[0115] (11) using a spin coating method to prepare a self-assembled small molecule layer 508 as a hole transport layer of the top battery;

[0116] (12) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 509 has a band gap of about 1.68 eV;

[0117] (13) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 510, thickness 20 nm;

[0118] (14) Using atomic layer deposition on C 60 A SnO2 electron transport layer 511 is deposited on the substrate at a deposition temperature of 100°C and a thickness of 20 nm;

[0119] (15) using magnetron sputtering to deposit a zinc-doped indium oxide transparent electrode 512 (IZO) with a thickness of 100 nm on the SnO2 electron transport layer;

[0120] (16) A metal silver electrode 513 is prepared on the back by screen printing; a silver electrode 514 is prepared on the front by high-temperature thermal evaporation on the zinc-doped indium oxide transparent electrode 512, both of which adopt a grid-line distributed electrode pattern design;

[0121] (17) Finally, a magnesium fluoride anti-reflection layer 515 with a thickness of 20 nm is deposited on the silver electrode 514 by high temperature thermal evaporation. Thus, the perovskite-crystalline silicon stacked solar cell with the passivated contact composite layer structure is formed. The cell has an effective area of ​​1 cm 2 The device can achieve a photoelectric conversion efficiency of 29.1%, which is 0.2% higher than the efficiency of the battery without ultra-thin metal layer in Example 2. The open circuit voltage, short circuit current density and fill factor are 1.825V and 20.2mA / cm respectively.2 , 78.91%.

[0122] Example 6

[0123] This embodiment provides a perovskite-crystalline silicon tandem solar cell having the passivation contact composite layer structure and a method for preparing the same. The tandem cell structure and the method for preparing the same given in this embodiment are as follows: Fig.12 and Fig.13 As shown. The stacked cell uses intrinsic a-Si:H(i) / nc-Si:H(p) as the hole passivation contact of the silicon bottom cell, superimposes a wide bandgap perovskite top cell, and uses grid-line silver electrodes on the front and back of the cell. The preparation method of the perovskite-crystalline silicon stacked cell is as follows:

[0124] (1) Select n-type single crystal silicon, use NaOH solution to etch and remove the damaged layer on the surface of the silicon wafer, then use diluted NaOH solution to make a texture and single-side alkaline polishing process and RCA cleaning to obtain an n-type silicon substrate 601;

[0125] (2) using ultraviolet ozone oxidation to oxidize a SiO2 tunneling layer 602 on the front surface of the silicon wafer at room temperature for 15 minutes and with a SiO2 thickness of 1.5 nm;

[0126] (3) The AZO layer 603 was prepared by ALD super-cycle method, with a deposition temperature of 200°C, a gas pressure of 50 mToor, a deposition cycle ratio of Al2O3 and ZnO of 24:1, a super-cycle number of 1, and an AZO thickness of 5 nm; an Al2O3 cap layer was deposited by ALD (which would be removed later). Fig.12 Not shown), the deposition temperature is 200°C, the gas pressure is 50 mToor, and the deposition cycle number is 300;

[0127] (4) The sample was placed in an atmosphere annealing furnace and annealed for 30 min at 500 °C in a N2 / H2 (95% / 5%) atmosphere;

[0128] (5) Prepare 0.1 M Na2CO3 solution, heat it to 60 °C, and immerse the sample in the solution for 8 min to remove the Al2O3 capping layer so as to form good contact later;

[0129] (6) depositing an a-Si:H(i) passivation layer 604 on the back side of the n-type silicon substrate 601 by PECVD process, with a thickness of 5 nm and a deposition temperature of 200° C.;

[0130] (7) depositing a boron-doped nc-Si:H(P) layer 605 on the back side by PECVD process with a thickness of 10 nm and a deposition temperature of 170°C;

[0131] (8) Depositing an ITO transparent electrode 606 on the back side by magnetron sputtering with a thickness of 110 nm;

[0132] (9) Printing a silver electrode 607 on the back side by a low-temperature silver paste screen printing process, and then drying it in air at 200°C to form a shape;

[0133] (10) using a spin coating method to prepare a self-assembled small molecule layer 608 as a hole transport layer of the top battery;

[0134] (11) Preparation of wide bandgap Cs by spin coating 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 The perovskite light absorbing layer 609 has a band gap of about 1.68 eV;

[0135] (12) Deposition of C on perovskite by high temperature thermal evaporation 60 Electron transport layer 610, thickness 20 nm;

[0136] (13) Atomic layer deposition was used to deposit C 60 A SnO2 electron transport layer 611 is deposited on the substrate at a deposition temperature of 100°C and a thickness of 20 nm;

[0137] (14) depositing a zinc-doped indium oxide transparent electrode 612 (IZO) with a thickness of 100 nm on the SnO2 electron transport layer by magnetron sputtering;

[0138] (15) preparing a silver electrode 613 on a zinc-doped indium oxide transparent electrode 612 by high temperature thermal evaporation;

[0139] (16) Finally, a magnesium fluoride anti-reflection layer 614 with a thickness of 20 nm is deposited on the silver electrode 613 by high temperature thermal evaporation.

[0140] Thus, a perovskite-crystalline silicon tandem solar cell having the passivation contact composite layer structure is formed.

[0141] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A passivation contact composite layer, characterized in that: The passivation contact composite layer structure is arranged on the surface of the silicon substrate, including a SiO2 tunneling layer, a ZnO-based electron selective transport layer and a hydrogen passivation cap layer deposited in sequence; the hydrogen passivation cap layer includes Al2O3, TiO2 and SiN x One or more of the above, the hydrogen passivation cap layer is removed by wet removal or dry etching or not; the wet removal method is a sodium carbonate solution heating immersion treatment.

2. The passivated contact composite layer according to claim 1, characterized in that: The ZnO-based electron selective transport layer is selected from an intrinsic ZnO layer or a doped ZnO layer.

3. The passivated contact composite layer according to claim 2, characterized in that: In the doped ZnO layer, the doping element is selected from one or more of Al, B, Ga and H, and the doping atomic concentration is 1-20%.

4. The passivated contact composite layer according to claim 3, characterized in that: The ZnO-based electron selective transport layer is deposited by atomic layer deposition, and the thickness and doping concentration of the doped ZnO layer are controlled by the number of super cycles in the atomic layer deposition super cycle mode and the cycle ratio in the doping sub-cycle.

5. The passivated contact composite layer according to claim 4, characterized in that: The doping element is Al, the doping cycle ratio of ZnO to Al2O3 in the atomic layer deposition super cycle mode is 5-100:1; the number of super cycles in the atomic layer deposition super cycle mode is 2-50 times; and the doping atomic concentration of the boron element is 1-20%.

6. The passivated contact composite layer according to claim 1, characterized in that: The silicon substrate is selected from a planar silicon substrate or a textured silicon substrate.

7. The passivated contact composite layer according to claim 1, characterized in that: The thickness of the ZnO-based electron selective transport layer is 1-200 nm, the thickness of the SiO2 tunneling layer is 0.5-2 nm, and the thickness of the hydrogen passivation cap layer is 5-200 nm.

8. The passivated contact composite layer according to claim 1, characterized in that: The preparation method of the SiO2 tunneling layer is a dry method or a wet method; the dry method is selected from thermal oxidation, ozone oxidation or chemical vapor deposition, and the wet method is selected from nitric acid oxidation.

9. The passivated contact composite layer according to claim 1, characterized in that: The hydrogen passivation cap layer may be stacked with a high electron concentration interface layer, and the high electron concentration interface layer is MgO x , metal Mg, metal Al or metal Ti.

10. A perovskite-crystalline silicon tandem solar cell, characterized in that: The light-receiving surface of the silicon bottom cell of the perovskite-crystalline silicon tandem solar cell has the passivation contact composite layer described in any one of claims 1-9.

Citation Information

Patent Citations

  • Electron selective passivation contact structure, solar cell and preparation method

    CN114678430A

  • An electronically passivated contact structure and a crystalline silicon solar cell

    CN114937707A

  • Transparent conductive passivation contact structure of silicon-based heterojunction solar cell and preparation method of transparent conductive passivation contact structure

    CN117558831A

  • Solar cell with graded doped passivation contact structure

    CN118507541A

  • Electron selective passivation contact structure and application thereof

    CN118899346A